The Potential of Sponge-Associated Bacillus spp. as A Biocontrol Agent to Inhibit Several Bacteria from Infected Catfish (Clarias gariepinus Burch) - Risky Hadi Wibowo; Sipriyadi Sipriyadi; Welly Darwis; Ardinan Pribadi; Novi Susianti; Della Indah Medani; Nadya Rosianti; Gustina Dwi Wulandari (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2023)
Catfish farming has been increasingly threatened by outbreaks of diseases caused by bacteria which are major problems for Indonesia’s catfish industry. This can lead to a decrease in the food quality of freshwater fishery products, especially catfish. In catfish farming, the occurrence of diseases can cause severe financial losses. This study aimed to identify bacteria that infected catfish and discover new potential antibacterial agents from Bacillus spp. isolated from a marine sponge to inhibit several bacteria from the infected catfish. Catfish samples were obtained from catfish farming with clinical observation of ulcerative lesions on the outside of the body. Several bacteria were isolated from the catfish and used sponge-associated bacterium to inhibit them in which using two methods namely spot assay and disc diffusion assay. Bacterial supernatant and pellet were used to performed antibacterial assay using disc diffusion method. These bacterial isolates were identified through their colony morphology, Gram staining, biochemical assays, and 16S rRNA gene sequence. Bacterial identification based on the 16S rRNA gene sequence showed that GL1 was 99.92% closely related to Aeromonas jandaei, HL1 was 100% closely to Bacillus amyloliquefaciens, and GL2 and HL2 was closely related to Bacillus cereus. The results of antibacterial assay indicated that sponge-associated Bacillus spp. successfully inhibited some bacteria that associated with infected catfish. In addition, Bacillus velezensis APD10 exhibited the most potential strain with antibacterial property which could inhibit all bacteria from the diseased catfish.